Supporting Heterogeneity and Congestion Control in Peer-to-Peer Multicast Streaming - Padmanabhan, Venkat; Wang, Helen; Chou, Philip A. (Int'l Workshop on Peer-to-Peer Systems, 2004)
We consider the problem of supporting bandwidth heterogeneity and congestion control in the context of P2P multicast streaming. We identify several challenges peculiar to the P2P setting including robustness concerns arising from peer unreliability and the ambiguity of packet loss as an indicator of congestion. We propose a hybrid parent- and child-driven bandwidth adaptation protocol that is designed in conjunction with a framework for robustness and that exploits application-level knowledge.